Efficacy of Shear-Wave Elastography for Detecting Postoperative Cervical Lymph Node Metastasis in Papillary Thyroid Carcinoma - Hye Jeong Kim; In Ho Choi; So-Young Jin; Hyeong Kyu Park; Dong Won Byun; Kyoil Suh; Myung Hi Yoo (International Journal of Endocrinology)
Aims. To evaluate shear-wave elastography (SWE) as a tool to detect postoperative cervical lymph node (LN) metastasis in patients with papillary thyroid carcinoma (PTC). Methods. Forty-three LNs of 43 patients with PTC undergoing ultrasound (US) and SWE before ultrasound-guided fine-needle aspiration (FNA) for the evaluation of postoperative cervical LN recurrences were analyzed. The mean (EMean), minimum (EMin), maximum (EMax), and standard deviation (ESD) of SWE elasticity indices were measured. Results. Among 43 indeterminate or suspicious LNs, 12 were malignant and 31 were benign. The EMean, EMin, EMax, and ESD values were significantly higher in malignant LNs than in benign LNs (EMean: 37.1 kPa in malignant versus 11.8 kPa in benign LNs, P<0.001; EMin: 11.3 kPa versus 5.1 kPa, P=0.046; EMax: 50.5 kPa versus 23.7 kPa, P<0.001; and ESD: 7.8 kPa versus 4.1 kPa, P=0.006). EMax had the highest accuracy (93.0%) when applied with a cut-off value of 37.5 kPa. It had a positive likelihood ratio of 25.83 and a diagnostic odds ratio of 150.0. Conclusions. The shear elasticity index of EMax, with higher likelihood ratios for malignant LNs, may help identify postoperative cervical LN metastasis in PTC patients with indeterminate or suspicious LNs.